Alternative Mechanisms of Astringency – What is the Role of Saliva?. Issue 5 (18th March 2013) - Gibbins, H.L.; Carpenter, G.H.
Abstract Astringency is described as a "dry puckering‐like sensation" in the mouth following consumption of tannins including tea polyphenols. The current model describing astringency is based on precipitation of salivary proline‐rich proteins by polyphenols and/or altered salivary lubrication. Because dryness from astringency is detected by oral tissues this suggests other interactions, possibly through direct alteration of the lubricating mucosal pellicle, which may also expose the oral mucosa below. A loss of mucosal lubrication is likely to be fundamental in astringency development and it seems likely that astringent stimuli alter the salivary bulk, saliva rheology and the saliva pellicle leading to an increase of friction in the oral cavity. Practical Applications For the consumer, high levels of astringency in foods may lead to them becoming unpalatable. However, as the health benefits of many plant‐based astringent molecules, such as polyphenols, have become more apparent there is a desire to increase their levels in the diet. Currently, because of the complexity of astringency and the likelihood of multiple mechanisms occurring simultaneously, there is still a gap in knowledge regarding how these mechanisms affect each other and how these lead to altered mouthfeel after consumption of astringent stimuli. A good understanding of astringency development in the oral cavity may lead to an advancement of mechanisms that may prevent the astringency without reducing levels of the astringent molecules in food.